2021
DOI: 10.1002/jccs.202100064
|View full text |Cite
|
Sign up to set email alerts
|

2‐Hydroxy‐5‐nitropyridine and 5‐nitro‐2‐pyridone: Tautomerism, infrared, Raman, and NMR spectral interpretations, normal coordinate analysis, and DFT calculations

Abstract: Raman (3700-50 cm À1 ) and infrared (IR) (4000-230 cm À1 ) spectra of 2-hydroxy-5-nitropyridine (HNP; C 5 H 4 N 2 O 3 ) have been recorded in the solid phase in addition to 1 H, 13 C, and 15 N nuclear magnetic resonance (NMR) spectra of the sample in dimethyl sulfoxide-d 6 (DMSO-d 6 ). Initially, keto and enol tautomeric forms were proposed owing to proton transfer from the hydroxyl group to pyridine nitrogen atom. Quantum mechanical calculations based on density functional theory (DFT; B3LYP, ωB97XD, and mPW1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…2-Hydroxy-5-nitropyridine may exist as two keto-eno tautomers (see Figure 12 ). Its NMR parameters were calculated and it was found that they fitted best with the keto-form [ 31 ], although the NMR parameter possibly should have been averaged, as the energy difference between the two tautomers was as low as 1.35 Kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Hydroxy-5-nitropyridine may exist as two keto-eno tautomers (see Figure 12 ). Its NMR parameters were calculated and it was found that they fitted best with the keto-form [ 31 ], although the NMR parameter possibly should have been averaged, as the energy difference between the two tautomers was as low as 1.35 Kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…2-Hydroxy-5-nitropyridine may exist as two keto-eno tautomers (see Figure 12). Its NMR parameters were calculated and it was found that they fitted best with the keto-form [31], although the NMR parameter possibly should have been averaged, as the energy difference between the two tautomers was as low as 1.35 Kcal/mol. For benzo[d,e]cinnoline, a good fit was found between 1 H calculated chemical shifts (B3LYP/6-311++G(d,p) for both structure and for GIAO calculations) and experimental values for the tautomer, which are shown in Figure 13.…”
Section: Tautomerismmentioning
confidence: 99%
“…In summary, the DFT-based chemical shift predictions reasonably approximated the lactam and lactim 19 F chemical shifts and were consistent with the chemical shift trends observed with solvent polarity, assuming the tautomer equilibrium shifts toward lactam with increased polarity. 38,39,51 The effects of various substituents at position 3 on 19 F chemical shift trends could also be reproduced. A more detailed analysis of the tautomer equilibrium would require the use of explicit solvents.…”
mentioning
confidence: 95%
“…16 c ,18 Experimental and theoretical analysis of tautomerism of 3- and 5-nitro-2-pyridone showed the dominance of the lactam form in the solid state and in solution. 16 d ,19 In the case of 4-pyridone in solution, an electronegative substituent, such as chlorine, and electron-withdrawing groups, such as aldehyde and ester, favour the lactim tautomer when placed at position 2. 16 a ,20 However, little effect on the tautomeric equilibrium of 4-pyridone was observed for substituents at position 3 (NH 2 , Cl and NO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we present results of our computational work performed with the aim to get a deeper understanding of pyridone tautomerism, and substituent and solvent effects on it. As substituents, we have chosen the already studied chlorine atom, 16,17 the less studied amino 16 c , d ,18,21 and nitro 16 d ,19,21 groups, and unexplored fluorine atom which is an important bioisostere of hydrogen atom. 32 The choice of substituents also includes the most important combination of inductive (I) and resonance (R) effects: −I and −R (NO 2 ), −I and +R with predominant induction (F and Cl) and −I and +R with predominant resonance effect (NH 2 ).…”
Section: Introductionmentioning
confidence: 99%